Manual: Public Finance and Employment Database - Kraan, Dirk-Jan (OECD Working Papers on Public Governance, 2012)
The Budgeting and Public Expenditures Division of the Public Governance and Territorial Development Directorate of the OECD has developed a database of public expenditures according to spending purpose. The classification used resembles closely the international COFOG classification and is therefore called "COFOG-Special". The database includes general government and all sub-sectors (central government, states, local government, and social security). In addition, a new approach has been developed for the estimation of employment in the public domain, as part of the work programme of the Public Employment and Management Working Party of the Public Governance Committee. The new approach is consistent with the National Accounts. In 2007, the expenditure database and the employment database were merged, and extended with revenues data. The COFOG-Special classification was maintained. The merged database was renamed the Public Finance and Employment Database (PFED) and is intended as a research tool for future OECD work and for use by the worldwide research community. This manual describes the contents of the PFED, explains the COFOG-Special classification, and contains an exhaustive treatment of the methodology